Beside herself - LaBan, Elizabeth (Lake Union Publishing, 2019)
"With her signature wit and charm, bestselling author LaBan shows how marriage doesn't necessarily follow a straight line, and unexpected detours might just bring a person back to the place he or she most wants to be."--